Pengaruh Work Life Balance dan Person Job Fit terhadap Affective Organizational Commitment dengan Mediasi Job Satisfaction pada Generasi Z di Yogyakarta - Maulana Muhammad Annazar; Didik Subiyanto; Mohammad Ahyar Syafwan Lysander (Journal of Economics and Management Scienties, 2026)
This study investigates how Work-Life Balance (WLB) and Person-Job Fit (PJF) shape Affective Organizational Commitment (AOC), with Job Satisfaction (JS) positioned as a mediating mechanism, among Generation Z workers in Yogyakarta, Indonesia. Employing a quantitative survey design, this study gathered data from 100 respondents selected through purposive sampling, with SEM-PLS serving as the analytical framework implemented through SmartPLS 4.0. The findings reveal that WLB exerts no significant direct effect on either JS or AOC, whereas PJF demonstrates a strong positive and significant influence on both. JS positively and significantly predicts AOC and fully mediates the PJF–AOC relationship, but does not mediate the WLB–AOC path. These results underscore that alignment between individual capabilities and job demands constitutes a more decisive driver of affective commitment for Generation Z than Work-Life Balance alone. Practically, organizations are encouraged to embed person-job alignment considerations into recruitment, onboarding, and career development to cultivate sustained emotional attachment among Generation Z employees, while work-life balance initiatives should be implemented substantively and reinforced through consistent organizational culture.